Increasing Understanding Regarding Free Legal Aid in the Implementation of Women's Rights Protection - Kurnianingsih, Marisa; Aprilia, Lina; Dita Nadya Anastasya; Kuswardani, Kuswardani; Surbakti, Natangsa (Jurnal Dedikasi, 2024)
This community service is carried out to increase understanding regarding legal aid, which is one of the efforts to protect women's rights legally. Equality between women is the foundation of ensuring legal protection for women because it includes efforts to provide access to justice for all individuals. As a rule of law, Indonesia guarantees the safety of women's rights, including the right to access legal aid. This community service is carried out using the socialization method. Socialization is carried out by holding discussions covering issues such as gender crimes, the protection of women from violence and exploitation, as well as the need for effective responses to violations of women's human rights. The "equality before the law" principle is essential in ensuring justice, protecting human rights, and upholding fair laws. The free legal aid program is also seen as a solution to provide access to justice for all individuals, regardless of their financial condition and society's gender. This community service is the result of collaboration between the Legal Aid and Consultation Agency (BKBH) FH UMS and the Kadipiro Subdistrict in Surakarta, which is expected to provide benefits to the broader community, especially women who are economically disadvantaged and have insight into obtaining justice.